Harnessing Semantic Meaning for Cultural Preservation: Analysing Cultural Movements Using Punching Trackers - Zaman, Zaini Bin Kamarol (Journal of Ecohumanism, 2025)
Through the integration of a supplementary quantitative layer of data, this study aims to enrich conventional preservation methodologies, providing insights into the subtleties of Silat that may elude traditional approaches alone. By analysing punch velocity, speed, and the distribution of actions between the dominant and non-dominant hands, the research facilitates a deeper exploration of Silat’s fundamental principles and complexities, thereby contributing to a more holistic preservation of its intangible cultural heritage. This study investigates the utilisation of motion capture technology, combined with punching trackers, to augment the preservation of intangible cultural heritage, with a specific focus on the intricate movements inherent in Silat, a traditional martial art form. By employing punching trackers to capture and analyse key parameters such as punch velocity, frequency, speed, and manual dexterity during Silat performances, the research aims to offer a more comprehensive understanding of the nuanced dynamics within Silat movements. This interdisciplinary approach not only advances the field of cultural heritage preservation but also underscores the potential for technology to be integrated into the protection of traditional practices. The outcomes of this research hold promise for informing preservation strategies not only for Silat but also for other forms of intangible cultural heritage, thereby bridging the divide between technological advancements and traditional cultural practices.